Challenges faced by emerging farmers in the managing projects towards sustainable agricultural development in Capricorn District, Limpopo Province, RSA - Matlou, Ntebatse Yvonne (University of Limpopo, 2018)
The research investigated the challenges faced by emerging farmers in managing projects towards sustainable agricultural development in Capricorn District. The literature established the importance of project management in the context of sustainable agricultural development. In this regard, it was found that it is of extreme importance to support emerging farmers in managing agricultural projects where emerging farmers are engaged through a participatory approach in decision making processes for sustainable agricultural development. Further, this research seeks to investigate the factors that hinder project management from influencing emerging farmers to manage and sustain the agricultural projects in the area of the study. Data was collected through semi-structured interviews and questionnaires were distributed to the selected sample within the target population. The purposive sampling method was used to select the 16 project officers for interviews while questionnaires were distributed randomly for 30 emerging farmers in the Molemole and Polokwane Municipalities. The findings of the study suggest that most emerging farmers and project officers think that the lack of resources and training hamper the management and sustainability of agricultural projects. To conclude, it is expected that the recommendations will highlight strategies and policies that could be put in place to accelerate the management of agricultural projects and their sustainability in the Capricorn District.
Thesis (M. Dev.) -- University of Limpopo, 2018
Keywords: Sustainable agricultural development; Farmers; Agricultural development projects -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo; Farmers -- South Africa -- Limpopo